1973
DOI: 10.1002/ps.2780040316
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate flow into mycorrhizal roots

Abstract: Ectotrophic mycorrhizas have been studied intensively and their value to some tree species is well known. Endotrophic mycorrhizas have received less attention and their potential value to plants has only been fully substantiated within the last 12 years. Responses of the host to mycorrhizal infection seem always to be associated with improved phosphorus nutrition of the plant. The mechanism whereby this occurs is considered. There is evidence that the ultimate limitation on phosphorus uptake by a simple cylind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
116
2
5

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 299 publications
(135 citation statements)
references
References 14 publications
12
116
2
5
Order By: Relevance
“…Sanders & Tinker, 1973;Wilson, 1988). This, together with their widespread occurrence in natural ecosystems (St. John & Coleman, 1983), has led researchers to assume that they play an important role in natural plant communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sanders & Tinker, 1973;Wilson, 1988). This, together with their widespread occurrence in natural ecosystems (St. John & Coleman, 1983), has led researchers to assume that they play an important role in natural plant communities.…”
Section: Discussionmentioning
confidence: 99%
“…These apparent benefits are generally thought to result from improved phosphate uptake (Sainz & Arines, 1988;Wilson, 1988), since it is known that there is hyphal transport of P from beyond the root depletion zone (Sanders & Tinker, 1973). The cost to the plant is a transfer of carbohydrate to the fungus (Douds, Johnson & Koch, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…On average, plants that are colonized by AMF grow 3.1 times larger than do uncolonized control plants (Hoeksema et al 2010). Arbuscular mycorrhizal fungi are thought to be more efficient at scavenging for soil nutrients, owing to their larger surface-to-volume ratios (Sanders and Tinker 1973). This ability is particularly important for acquisition of P, which is relatively immobile in soil (Nye and Tinker 1977).…”
mentioning
confidence: 99%
“…Hardie & Leyton (1981) and Allen (1982) provided experimental support for a mechanism of direct water flow through hyphae. Others (Sanders & Tinker, 1973;Cooper & Tinker, 1981) have found that hyphae of VA mycorrhizas may not transport sufficient quantities of water to alter shoot water relations. Our in situ studies with green ash, under well watered conditions, indicate that external hyphae do not increase the elective length of seedling root systems.…”
Section: Discussionmentioning
confidence: 99%